Direct controls for wind turbine with PMSG used on the real wind profile of Essaouira-Morocco city - Dalila Hammoumi; Chakib El Bekkali; Mohammed Karim; Mohammed Taoussi; Najib El Ouanjli; Badre Bossoufi (Institute of Advanced Engineering and Science, 2019)
This article presents the use of a permanent magnet synchronous generator (PMSG) for the wind energy production and electrical energy injection produced into an electrical grid. The objective is to perform modeling and direct control of the Wind Energy conversion System (WECS), taking into account the problems of wind speed variations and generator maintenance. The direct torque control (DTC) is applied to the machine-side converter and direct power control (DPC) is applied to the grid-side converter. The performance of WECS is tested in MATLAB / SIMULINK environment simulation with a real wind profile of Essaouira-Morroco city. The simulation results obtained show that the proposed direct controls provide high performance in terms of setpoint tracking, speed, stability and power quality.